Hypercalciuria as a cause of persistent or recurrent haematuria. Issue 3 (March 1988) - Stark, H; Tieder, M; Eisenstein, B; Davidovits, M; Litwin, A
Abstract : Of 91 children with idiopathic persistent or recurrent haematuria, eight also had hypercalciuria. This was transient in three and persistent in five. Persistent hypercalciuria was a rare cause of microscopic haematuria (two of 80), but common in association with gross haematuria (three of 11).